Exponentially decreasing tooth growth rate in horse teeth: implications for isotopic analyses. (15th December 2014) - Bendrey, R.; Vella, D.; Zazzo, A.; Balasse, M.; Lepetz, S.
<x xml:space="preserve">Abstract</x> A range of archaeological and palaeoclimatic studies use isotopic analyses of ungulate hypsodont tooth enamel. Such studies commonly assume a constant growth rate, though this has not been fully tested. Here, we use stable isotope analyses of sequential enamel samples to study horse tooth growth. We fit the data using models corresponding to constant and exponentially decreasing rates of growth, and compare the results to metrical data showing the geometry and timing of apposition. The results indicate enamel apposition and maturation advances at an exponentially decreasing rate. An understanding of this variable growth rate is crucial for interpreting isotopic data from equid teeth.